Transcriptional control of Arabidopsis seed development - Verma, Subodh; Attuluri, Venkata Pardha Saradhi; Robert, Hélène S (Planta, 2022)
The entire process of embryo development is under the tight control of various transcription factors. Together with other proteins, they act in a combinatorial manner and control distinct events during embryo development. Seed development is a complex process that proceeds through sequences of events regulated by the interplay of various genes, prominent among them being the transcription factors (TFs). The members of WOX, HD-ZIP III, ARF, and CUC families have a preferential role in embryonic patterning. While WOX TFs are required for initiating body axis, HD-ZIP III TFs and CUCs establish bilateral symmetry and SAM. And ARF5 performs a major role during embryonic root, ground tissue, and vasculature development. TFs such as LEC1, ABI3, FUS3, and LEC2 (LAFL) are considered the master regulators of seed maturation. Furthermore, several new TFs involved in seed storage reserves and dormancy have been identified in the last few years. Their association with those master regulators has been established in the model plant Arabidopsis. Also, using chromatin immunoprecipitation (ChIP) assay coupled with transcriptomics, genome-wide target genes of these master regulators have recently been proposed. Many seed-specific genes, including those encoding oleosins and albumins, have appeared as the direct target of LAFL. Also, several other TFs act downstream of LAFL TFs and perform their function during maturation. In this review, the function of different TFs in different phases of early embryogenesis and maturation is discussed in detail, including information about their genetic and molecular interactors and target genes. Such knowledge can further be leveraged to understand and manipulate the regulatory mechanisms involved in seed development. In addition, the genomics approaches and their utilization to identify TFs aiming to study embryo development are discussed.
Keywords: Seeds; Transcription factors; regulace genové exprese u rostlin; Embryo patterning; Arabidopsis; transkripční faktory; Gene Expression Regulation, Plant; Arabidopsis Proteins; Transcription Factors; Maturation; semena rostlinná; proteiny huseníčku; Seed